Comparative Study of Solar Collector's Configuration on Ejector Refrigeration Cycle - SENJAYA (NIM 13104071), RAFFLES
Solar energy can be used as thermal energy source with solar collector apparatus. Thermal energy is used as the heat source for generator on an ejector refrigeration cycle. A high solar collector's performance is needed to change as high as possible solar energy become thermal energy so that the performance of the system is increase. Calculation method of heat transfer analysis for solar collector is needed to be developed to obtain the accurate performance analysis. Performance of three solar collector's configurations of solar collector's performance is analyzed from amount of heat capacity which can be absorbed from 08.00 until 17.00. The heat calculation refers to intensity of solar radiation which has been obtained by another researcher with assumption that the sky's condition at Bandung is clear. Heat transfer analysis at each collector is conducted to predict the performance of solar collectors. The analysis includes absorption of solar radiation, heat loss, and temperature distribution refers to the slope variation of collector. The result of this calculation is also compared with another research result to validate the accuracy of the calculation method in this study. The calculation result indicates the same tendency with another experimental result although there is a small deviation compared with an experimental result. For the same collector area, evacuated tubes solar collector can absorb energy more than the others with due to lower heat loss occur so that the higher outlet temperature of hot water can be achieved. Therefore, evacuated tubes solar collector is more suitable to be used as heat collector on ejector refrigeration cycle than the others.